2021
DOI: 10.3390/su13158204
|View full text |Cite
|
Sign up to set email alerts
|

Game-Based Learning in Project Sustainability Management Education

Abstract: Projects and project-based activities account for over 30% of the global GPD and act as significant vehicles in the transition towards a more sustainable future. Sustainability strategies are typically enacted and implemented through projects in project-based organisations and firms. Incorporating sustainability principles into the project, product, and service management processes with successful project decision making is a challenging task and requires new personnel competencies and skills. Project sustaina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 55 publications
(95 reference statements)
2
20
0
1
Order By: Relevance
“…The above findings elaborate on the previous understanding of the role of GBL methods in enabling practice-based learning in higher education for project management (Anastasiadis et al, 2018;Jääskä et al, 2021;Rumeser and Emsley, 2019;Jaccard et al, 2022) by highlighting that GBL methods are not just practical games but should include carefully planned simulative elements. This enables a realistic test environment where students can put theoretical project management lessons into practice to gain confidence through trial and error.…”
Section: Gbl Methods Enable Students To Understand the Real-life Impl...supporting
confidence: 59%
See 1 more Smart Citation
“…The above findings elaborate on the previous understanding of the role of GBL methods in enabling practice-based learning in higher education for project management (Anastasiadis et al, 2018;Jääskä et al, 2021;Rumeser and Emsley, 2019;Jaccard et al, 2022) by highlighting that GBL methods are not just practical games but should include carefully planned simulative elements. This enables a realistic test environment where students can put theoretical project management lessons into practice to gain confidence through trial and error.…”
Section: Gbl Methods Enable Students To Understand the Real-life Impl...supporting
confidence: 59%
“…Game features such as game structure, involvement, and appeal may motivate students and promote achieving desired learning outcomes (Garris et al, 2002;Huang et al, 2013;Jääskä et al, 2021;Breien and Wasson, 2021;Naul and Liu, 2020;Plass et al, 2015). Existing research has identified a positive impact of GBL on students' activation, motivation, and emotional behavior (Barbosa and de Ávila Rodrigues, 2020;de Freitas, 2018;Law, 2019;Vu and Feinstein, 2017), feelings of interest and immersion (Hamari et al, 2016;Schwabe and Göth, 2005), and student engagement (Hartt et al, 2020).…”
Section: Game-based Learning and Motivationmentioning
confidence: 99%
“…The use of game elements for learning purposes could be helpful. Moreover, games could facilitate the intentional and innovative embedding of sustainability principles in HEIs [96]. Our findings showed that GBL constitutes a powerful tool for HEIs in the training of valuable soft skills, such as teamwork competence and innovation.…”
Section: Discussionmentioning
confidence: 73%
“…It was found that the characteristics of a class structure, teaching style, and class environment could significantly motivate students and enhance class performance. Promoting affective learning, various pedagogies have been applied to enhance students’ interest, satisfaction and motivation (e.g., Durrani et al, 2022 ; Jääskä et al, 2021 ). Durrani et al (2022) illustrated an example which investigated the effect of flipped classrooms and gamification among 105 students via surveys and questionnaires.…”
Section: Results and Findingsmentioning
confidence: 99%